Antimicrobial-Resistant Escherichia coli Distribution and Whole-Genome Analysis of Sequence Type 131 Escherichia coli Isolates in Public Restrooms in Taiwan - Chang, Szu-Min; Chen, Jenn-Wei; Tsai, Chin-Shiang; Ko, Wen-Chien; Scaria, Joy; Wang, Jiun-Ling (Frontiers in Microbiology, 2022)
The threat of antibiotic-resistant bacteria to public health may originate from public restrooms. To better understand the community burden of antimicrobial-resistant Escherichia coli and sequence type complex 131 E. coli (STc131) in the public restroom, we performed a surveillance in public restrooms in southern Taiwan. Swabs were sampled from randomly selected public restrooms in Tainan, Taiwan in 2019. Antimicrobial susceptibility, phylogenetic grouping, and multiplex PCR were performed for the major ST complex in the B2 phylogenetic group. If STc131 isolates were identified, whole-genome sequencing was performed. A total of 613 collection sites found 132 sites (21.5 %) positive for E. coli. The most common phylogenetic group was A (30.9 %) followed by B2 (30.3 %). Ceftriaxone-resistant E. coli and extended-spectrum β-lactamases-producing E. coli were found in 2.4 % and 1.0 % of total public restrooms, respectively. The isolates in rural areas had higher ceftriaxone non-susceptibility than those in the city centers (3.9 % vs. 1.2 %, P = 0.038). Nine STc131 isolates were found in public restrooms, and most (77.8 %) belonged to the subtype fimH41 while 22.2 % belonged to fimH30. With the inclusion of STc 131isolates from human and dog fecal colonization in Taiwan, whole genome sequencing was performed in 35 isolates. A large cluster of fimH41 in SNP-tree and GrapeTree was found in different sources (human, dog, and environment) and geographical areas. In conclusion, our surveillance of antimicrobial-resistant E. coli in public restrooms showed that more drug-resistant E. coli exit in rural areas than in city centers. The whole-genome sequence implies that fimH41STc 131 strains are successfully circulated in the community in Taiwan.